Formation of carbon dioxide based gas hydrates - Pereira, Liliana Sofia Carqueijó (2022)
Carbon dioxide hydrates are compounds that form through a combination of CO₂ and H₂O molecules. Currently, carbon dioxide hydrates have one of the greatest potential applications in the areas of climate change, such as capture and storage of carbon dioxide or gas replacement in the exploitation of methane hydrates. These compounds have also been a major problem in the oil and natural gas industries because they cause pipeline blockages. To support their applications and solve the industrial problem, understanding the kinetics of carbon dioxide hydrates is one of the current challenges. In this context, this work is focused on the study of kinetics of CO₂ hydrate formation. CO₂ hydrates have been formed in a high pressure apparatus with an appropriate nucleation cell and mixing chamber. The experiments were performed with mixtures of carbon dioxide and water at temperature T = 283.4 ± 0.1 K and pressure p = 9.2 ± 0.1 K MPa, and have a carbon dioxide solubility in water of xCO₂ = 0.0294. The nucleation experiments were performed at 275.9 ± 0.1 K in pressure increments ranging from 9.5 to 33.0 MPa. The apparatus and the methodology were optimized and the results show a high reproducibility of gas hydrate formation. Focusing on carbon dioxide hydrate kinetics, a high dependence on the induction time and the nucleation rate as a function of Δp, is observed. From Δp = 9.5 MPa to Δp = 33.0 MPa, they can vary approximately from 1 to 370 s and from 5.47 x 10⁵ to 1.32 x 10⁸ m⁻³ s⁻¹, respectively. In these conditions, there were observed two nucleation regimes: heterogeneous nucleation, at Δp < 28.0 MPa and homogeneous nucleation, at Δp > 32.5 MPa. The regime change is found at Δp = [28.0 - 32.5] MPa. For heterogeneous nucleation, the kinetic and the thermodynamic parameters calculated are A = [4.9 ± 0.5] x 10⁶ m⁻³ s⁻¹ and B = 1.8 ± 0.2, respectively. For homogeneous nucleation, the kinetic and the thermodynamic parameters calculated are A = 3.9 x 10¹² m⁻³ s⁻¹ and B = 24.7, respectively. These conclusions support the classical nucleation theory. However, a more comprehensive and systematic studies are still needed to understand nucleation process and support these considerations. To solve the current challenges, additional efforts can be made, for example, considering hydrate memory effect when reusing the carbon dioxide and water mixture and other apparatus optimisations.